FROM RITUAL COMMUNITY TO POLITICAL ACTOR: THE TRANSFORMATION AND POWER STRATEGIES OF THE KHALWATIYAH SAMMAN ORDER IN SOUTH SULAWESI - Arif, Muhammad; Syatar, Abdul; Husni, Muhammad; Ilham, M.; Ashufah, Abdul Hayyaqdhan (Jurnal Al-Dustur, 2025)
This article investigates how politics functions not merely as an external arena of pressure but as a medium of institutional survival for the Khalwatiyah Samman Order in South Sulawesi. While existing studies on Indonesian Sufi orders have predominantly emphasized doctrinal teachings, ritual systems, and patterns of social expansion, they tend to overlook the political mechanisms through which a tarekat negotiates authority, confronts accusations of heresy, and constructs long-term legitimacy within shifting power structures. Addressing this gap, the study focuses on two pivotal historical events—the 1931 heresy accusation issued by King Bone La Mappanyukki and the 1958 ulama assembly organized by the DI/TII movement in Wanua Waru—to demonstrate that the Khalwatiyah Samman Order has continuously acted as both a religious and socio-political institution capable of adapting to, resisting, and strategically engaging competing forces such as monarchy, colonialism, and radical Islamist militancy. Using a qualitative, descriptive-historical method based on manuscripts, archival sources, and oral testimonies, the research reveals that the tarekat’s endurance is sustained through three interconnected strategies: cultural accommodation within local power structures, intellectual-theological argumentation to counter delegitimization, and the mobilization of a broad follower base as a source of social capital. These strategies not only defend its orthodoxy but also allow the tarekat to convert political threats into opportunities for institutional consolidation. The article therefore argues that politics, in this context, is not solely a site of contestation but a resource for identity affirmation and doctrinal continuity, offering a new analytical lens for understanding Sufi orders in Indonesia as adaptive actors with historical agency in the negotiation of religious and political authority.